Models for technology choice in a transit corridor with elastic demand. (October 2017) - Moccia, Luigi; Giallombardo, Giovanni; Laporte, Gilbert
Highlights: We present two optimization models for a transit line with elastic demand. These models allow a strategic comparison of mode choices. We devise an equivalence scheme between fixed and elastic demand models. Elastic demand does not change the conclusions offered by a fixed demand model. Profit maximization yields half captured demand than social welfare maximization. Abstract: We present two optimization models for a transit line under the assumption that the demand is elastic and can be approximated by a linear function of fare and passenger travel time components. These models can be used to strategically evaluate technology choices. We study the effect of demand elasticity on the technology choice by analytic and numerical comparison with some fixed demand models. We assume a range of objective functions having as two extrema the maximization of operator's profit and the maximization of social welfare. We show both analytically and numerically that accounting for demand elasticity does not change the conclusions that can be derived by an equivalent fixed demand model. This invariance holds for a broad range of objective functions in the elastic case. The significant difference between the two objective function extrema lies in the proportions of captured demand.